ASSESSMENT OF THE EFFECT OF DIFFERENT TURBULENT CLOSURE SCHEMES ON SIMULATING THE SEA SURFACE TEMPERATURE IN THE CENTRAL REGION OF VIETNAM’S EAST SEA - Vui, Vu Thi; Cuong, Nguyen Kim; Huan, Nguyen Minh (Vietnam Journal of Marine Science and Technology, 2016)
In this paper, the ROMS model was used to simulate the sea surface temperature (SST) in the central region of Vietnam’s East Sea. Two turbulent closure schemes: Brunt-Vaisala and KPP were applied with the same conditions in order to compare the differences and the ability for using them. The simulated SST fields were compared and in good agreement with the mechanism maps of SST. The suggestions for using these schemes were analyzed. This result raises a question and answers how to choose a better closure scheme to apply in simulating SST. The solved problem is very necessary for applying numerical models to simulate SST field.